Critical Theory for Library and Information Science Exploring the Social from Across the Disciplines - Hjørland, Birger (Dansk Biblioteksforskning, 2010)
ANMELDELSE: Leckie, Gloria J., Lisa M. Given, and John E. Buschman (red.) (2010). Critical Theory for Library and Information Science: Exploring the Social from Across the Disciplines. Westport, Conn.: Libraries Unlimited.